2021
DOI: 10.15295/bmij.v9i1.1773
|View full text |Cite
|
Sign up to set email alerts
|

Examining consumer use of mobile health applications by the extended UTAUT model

Abstract: Today, rapid changes and innovations in technology cause changes in the health sector as in many areas. Especially mobile technologies and applications are increasing their usage areas in the health sector day by day. Thanks to these mobile health applications, consumers provide a lot of convenience and advantages in healthy eating, reproductive health, disease monitoring, access to health records, etc.The study aims to investigate consumers’ usage of mobile health (mHealth) applications with the extended Unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 40 publications
11
29
0
Order By: Relevance
“…The results indicate that consumers give a lot of importance to the hedonic aspect. Similar results were seen by Chau et al [67], Nikolopoulou et al [68], and Semiz and Semiz [69]. On the other hand, an empirical study by Handoko [70], and Alfansi and Daulay [71] shows hedonic motivation does not affect behavioral intention.…”
supporting
confidence: 81%
“…The results indicate that consumers give a lot of importance to the hedonic aspect. Similar results were seen by Chau et al [67], Nikolopoulou et al [68], and Semiz and Semiz [69]. On the other hand, an empirical study by Handoko [70], and Alfansi and Daulay [71] shows hedonic motivation does not affect behavioral intention.…”
supporting
confidence: 81%
“…In the UTAUT model, Venkatesh et al (2003) proposed and confirmed that performance expectancy had a significant positive effect on individuals' behavioral intentions. Semiz and Semiz (2021) also reported that performance expectancy had an important impact on users' intention to use mHealth Apps in their survey. Mobile healthcare can provide users with timely and valuable information resources, which can significantly reduce the time for users to queue for registration, saving much time, energy and physical costs.…”
Section: Performance Expectancymentioning
confidence: 94%
“…In fact, the particularity of mHealth services makes subjective norm play a very important role in users’ intention of adoption. When important persons (relatives, friends, experts) recommend them to use mHealth services, their trust in products or services will be significantly improved, and the intention to use mHealth will be stronger ( Semiz and Semiz, 2021 ). In summary, this study proposes the following hypothesis:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The advocacy of this theoretical model can add to the existing literature review as it diversifies the aspects that influence the adoption of mHealth applications along with the mediating effect of intention to use such services. The UTAUT model that has been chosen for conducting the current study is extensively used by numerous scholars in performing studies related to the customers’ acceptance of new and emerging technologies (Petersen et al, 2020; Semiz & Semiz, 2021). Ndayizigamiye et al (2020) found in their research that social influence, facilitating conditions, awareness, performance expectancy, effort expectancy, behavioral intention, and usage behavior variables might drive the acceptability of mHealth applications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Performance expectancy is the intensity of confidence of a smartphone user regarding enhancing performance in following healthier eating habits and diet patterns through mHealth applications (Alam et al, 2020; Semiz & Semiz, 2021). It may be simply characterized as to how much one feels that using a particular approach may help increase work performance.…”
Section: Literature Reviewmentioning
confidence: 99%